An integrated public art in Putrajaya urban landscape / Alamah Misni and Anwar Suran - Misni, Alamah; Suran, Anwar (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
The art found in public space represents a local social and cultural situation, as well as the artistic and aesthetic tendencies. There is a close relationship between the public art and the city landscape. Public art is part of the broader visual environment of buildings, landscapes, and infrastructure. It can promote a sense of place, contribute to legibility or wayfinding, and support efforts to quality urban design. It can be in the form of sculpture, street furniture, mural, and even fountain structure. This research focuses on the user's perception and appreciation of integrated public art in the Putrajaya urban landscape. Data was collected using qualitative and quantitative methods. The case study data collections were conducted through a survey, observation, and distribution of questionnaires. The case study was carried out in the Putrajaya urban landscape. Putrajaya was selected as a case study because it is the new administrative capital of Malaysia that has seen the need to be distinctively outstanding in both its characteristics and development. Putrajaya has revealed the influence of public art in enforcing and strengthening the identity of the city. Subsequently, the recommendation has been made to enhance the planning process and management system by the local authority in the Putrajaya urban landscape. Therefore, this research will help to generate the social awareness and understanding of the effort of integrating public art into the Malaysian urban landscape.